Needs analysis study of Malaysian primary and secondary in-service Science teachers on the use of English in teaching Science - Siti Maftuhah Damio; AMIR, Aisyah Insyirah; Mohamad, Nur Alyaa Liyana (Fakultas Ilmu Budaya, Universitas Brawijaya, 2024)
An announcement of a pivotal decision: reinstating English as the medium of instruction for Mathematics and Science subjects in Malaysia took place in 2020 through Dual Language Programme.This move aimed to bolster language proficiency within the education system, a vital stride in educational reform. Recognizing the imperative for Malaysian students to gain enhanced exposure to English across subjects, this report delves into an analysis of how Science teachers in Malaysia incorporate English in their classrooms, aligned with the principles of English for Specific Purposes (ESP). Utilizing data collected through an online questionnaire, this study assesses teachers' English proficiency in teaching Science. Results from present and target situation analyses reveal that a majority of teachers self-rate their English proficiency at the B1 (Intermediate) level. These findings underscore teachers' awareness of the need to enhance their English skills to enrich the learning environment for students. The report presents comprehensive data, findings, and discusses potential implications, providing recommendations to empower teachers in delivering more effective Science instruction in English moving forward.